Infectious virus in exhaled breath of symptomatic seasonal influenza cases from a college community - Yan, Jing; Grantham, Michael; Pantelic, Jovan; de Mesquita, P. Jacob Bueno; Albert, Barbara; Liu, Fengjie; Ehrman, Sheryl; Milton, Donald K. (Proceedings of the National Academy of Sciences - PNAS, 2018)
Little is known about the amount and infectiousness of influenza virus shed into exhaled breath. This contributes to uncertainty about the importance of airborne influenza transmission. We screened 355 symptomatic volunteers with acute respiratory illness and report 142 cases with confirmed influenza infection who provided 218 paired nasopharyngeal (NP) and 30-minute breath samples (coarse >5-μm and fine ≤5-μm fractions) on days 1–3 after symptom onset. We assessed viral RNA copy number for all samples and cultured NP swabs and fine aerosols. We recovered infectious virus from 52 (39%) of the fine aerosols and 150 (89%) of the NP swabs with valid cultures. The geometric mean RNA copy numbers were 3.8 × 10⁴/30-minutes fine-, 1.2 × 10⁴/30-minutes coarse-aerosol sample, and 8.2 × 10⁸ per NP swab. Fine- and coarse-aerosol viral RNA were positively associated with body mass index and number of coughs and negatively associated with increasing days since symptom onset in adjusted models. Fine-aerosol viral RNA was also positively associated with having influenza vaccination for both the current and prior season. NP swab viral RNA was positively associated with upper respiratory symptoms and negatively associated with age but was not significantly associated with fine- or coarse-aerosol viral RNA or their predictors. Sneezing was rare, and sneezing and coughing were not necessary for infectious aerosol generation. Our observations suggest that influenza infection in the upper and lower airways are compartmentalized and independent.